2002
DOI: 10.1016/s1044-0305(02)00343-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for long-range glycosyl transfer reactions in the gas phase

Abstract: A long-range glycosyl transfer reaction was observed in the collision-induced dissociation Fourier transform (CID FT) mass spectra of benzylamine-labeled and 9-aminofluorene-labeled lacto-N-fucopentaose I (LNFP I) and lacto-N-difucohexaose I (LNDFH I). The transfer reaction was observed for the protonated molecules but not for the sodiated molecules. The long-range glycosyl transfer reaction involved preferentially one of the two L-fucose units in labeled LNDFH I. CID experiments with labeled LNFP I and labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 61 publications
4
61
0
Order By: Relevance
“…It involves initial protonation of the derivative, presumably on the amine group linking the carbohydrate and derivative. Similar fucose migrations have been reported in the CID spectra of protonated benzylamine-(2/9) and 9-aminofluorene-(7) labeled carbohydrates (Franz & Lebrilla, 2002). These rearrangement ions are absent from the fragmentation spectra of sodiated ions (Franz & Lebrilla, 2002;Harvey et al, 2002), emphasizing the advantage of using alkali metalcatonized ions in investigations of the structure of new compounds.…”
Section: Internal Residue Lossessupporting
confidence: 74%
“…It involves initial protonation of the derivative, presumably on the amine group linking the carbohydrate and derivative. Similar fucose migrations have been reported in the CID spectra of protonated benzylamine-(2/9) and 9-aminofluorene-(7) labeled carbohydrates (Franz & Lebrilla, 2002). These rearrangement ions are absent from the fragmentation spectra of sodiated ions (Franz & Lebrilla, 2002;Harvey et al, 2002), emphasizing the advantage of using alkali metalcatonized ions in investigations of the structure of new compounds.…”
Section: Internal Residue Lossessupporting
confidence: 74%
“…Haverkamp and co-workers demonstrated that CID of sodiated precursor ions ([M þ Na] þ ) did not yield any product ions that involved the loss of an internal residue (Kováčik et al, 1995;Brüll et al, 1998). Identical observations were reported from CID-experiments performed in a matrix-assisted laser desorption ionization (MALDI) Fourier transform ion cyclotron resonance (FTICR) system by Franz and Lebrilla (2002): lacto-N-fucopentaose I labeled with benzylamine (BA) yielded product ions with IRL only after fragmentation of the protonated precursor ion, and not with the sodiated analogue (Fig. 2).…”
Section: Influence Of Adductsmentioning
confidence: 78%
“…As mentioned earlier, the rearrangement process is often described as the loss of an internal residue (moiety B), or alternatively as the transfer or migration of a monosaccharide (e.g., transfer of A À C). Next to the loss of a single internal residue, rearrangements have been reported which involve the loss of multiple internal residues (Ernst, Müller, & Richter, 1997;Franz & Lebrilla, 2002;Broberg, 2007). In these cases, transfer is often the preferred term, as in the case of long-distance migration observed in fucose (Fuc) rearrangements (see Section VII).…”
Section: Systematics and Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…The fragmentation pattern was dominated by fragment ions retaining the modified reducing terminus, thus simplifying the interpretation of the mass spectral data. More recently, the behavior of oligosaccharides derivatized with benzylamine in CID Fourier transform experiments has been reported [44]. In addition, derivatization of oligosaccharides with benzylamine was also used in a capillary electrophoretic method for the separation of oligosaccharides [45].…”
Section: Introductionmentioning
confidence: 99%